Rekonsiliasi Waris Tiga Dimensi - Faizah, Isniyatin; Shodiq, Ja’far; Muhibbulloh, Muhammad Za'im; Gufron, Muhammad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This research examines legal pluralism in Indonesian inheritance law, encompassing three parallel systems: Islamic law (sharia), customary law (adat), and civil law (KUHPerdata). Dutch colonial legacies created normative tensions, including the 2:1 faraidh ratio, collectivist customary principles (Minangkabau matrilineal systems or Batak patrilineal systems), and the Civil Code's egalitarian framework, often precipitating familial disputes. Employing a normative-comparative methodology, this study analyzed statutes, jurisprudence, and key real-world cases, such as the 1957 Minangkabau case and Lamtiur v. Hariman (1971). Findings stressed that the command for grounded reconciliation in tolerance and maqashid syariah to harmonize core values. This harmonization can could be achieved through contextual ijtihad, customary deliberation, mediation, and testamentary grants instruments. This research is an integrative multidimensional model that provides a progressive framework for achieving substantive justice, reducing litigation, and reinforcing social cohesion in this pluralistic society. This research recommended judicial reform, legal education, and socialization of pluralism to bolster national stability